Complete Digital Workflow for Evaluation of the Three‐Dimensional Monson's Sphere Using Digital Scanning - Cheng Wen; Huan Huan Wang; Huo Jia Muhetaer; Fan Xie; Rui Han; Jin Cheng Wu (Clinical and Experimental Dental Research)
ABSTRACT Background As a combination of curve of Spee and curve of Wilson, the Monson sphere reflects the arrangement of teeth in three‐dimensional (3D) space. For occlusal analysis, the Monson sphere can provide an important reference for prosthetic reconstructions or orthodontic treatments. Objectives The purpose of this study was to generate and investigate the 3‐D Monson sphere through a complete digital workflow with intraoral scanning models and custom software. Material and Methods Sixty‐four Chinese adults (32 males and 32 females) with individual normal occlusion were recruited, and their intraoral scanning models were obtained using a digital intraoral scanner. Twenty‐six landmarks on the scanning models were digitized using a reverse engineering software. Monson's sphere was generated and evaluated by fitting a sphere to the cusp tips using a least‐squares method by means of custom software program. Mann–Whitney's U test was performed to test the radius difference of Monson's sphere between males and females. One‐sample t‐test was used to test the statistical significance (α = 0.05). Results Monson's sphere could be generated by means of digital scanning combined with customed software. The mean radius of Monson's sphere was 77.35 ± 13.38 mm, which was lower than the theoretical value proposed by Monson. Furthermore, there were significant differences between males and females in Monson's sphere radius (p < 0.001). Conclusions This study explores a new best‐fit algorithm for generating 3‐D Monson's sphere by complete digital workflow. The radius of Monson's sphere in Chinese adults was lower than the classical value of four‐inch proposed by Monson. There was a significant difference between males and females. Monson's sphere value found in this study could be used as a reference for prosthetic reconstruction and orthodontic treatment and be applied to improve dental treatment results.